Epidemiological Characteristics of Trauma Patients Maxillofacial Surgery at the Hospital Geral de Blumenau SC From 2004 to 2009 - Martins, José Carlos, Junior; Keim, Frederico Santos; Helena, Ernani Tiaraju de Santa (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Accidents involving the face have increased incidence in the last four decades. The medical literature refers to the increase in motor vehicle collisions and urban violence as the major causes of injuries, especially in young individuals.Objective: Raise the epidemiological profile of 222 patients with facial fractures at the Hospital Santo Antonio from 2004 to 2009.Method: Case study with retrospective analysis of records of patients diagnosed with facial fractures. Several variables were considered: gender, age, occupation, education level, origin, location and number of bones involved, etiology, and mean hospital stay of patients.Results: The male sex predominated with 178 cases (80.1%), the average age was 29.6 years, 86 (38.73%) had a steady job. Unmarried 178 cases (80.18%). Primary school predominated among the patients, 74 (33.34%), and most live in the city of Blumenau, 175 (78.82%). The assault was primarily responsible for the surgical indication in 79 cases (35.58%), involving a bone in 193 cases (86.9%). The main bone involved was the mandible in 90 cases (40.54%). The average length of stay was 2.5 days.Conclusions: The epidemiological profile of 222 patients is an individual male, aged 20-29 years old, unmarried, low education and employee. The most prevalent etiology was assault, involving a bone, the mandible being the most involved bone.
Keywords: epidemiology; maxillofacial injuries; bone fractures